Marketing case studies : linking theory to practice - Irshaidat, Rand (Washington, Wash. : Academica Press, 2023)
"Sure to become a leading textbook for business students, Marketing Case Studies includes 25 pedagogical case studies encountered by contemporary firms in the realms of marketing management, integrated marketing communication, consumer behavior, branding, customer relationship marketing (CRM), and more. It offers an academic reference to marketing students, instructors, and practitioners. Each case study is followed by questions and proposed answers, which present detailed literature on the topic, followed by execution of theories and models"--
Keywords: Marketing management -- Case studies; Marketing -- Case studies